ACORDO SOBRE BIODIVERSIDADE MARINHA PARA ALÉM DA JURISDIÇÃO NACIONAL (BBNJ): REGIME JURÍDICO INTERNACIONAL DE UTILIZAÇÃO SUSTENTÁVEL DOS RECURSOS GENÉTICOS MARINHOS DO ALTO MAR E DA ÁREA - Toledo, André de Paiva; Bizawu, Kiwonghi (Veredas do Direito, 2021)
The United Nations participates in the construction of the marine legal system. At its third conference on the Law of the Sea, the United Nations Convention on the Law of the Sea (UNCLOS) was adopted, which, having provisions related to biodiversity, does not expressly address genetic resources. In view of this, the United Nations convened a conference to negotiate an Agreement on the conservation and sustainable use of marine biodiversity beyond the national jurisdiction (BBNJ), which began in 2018. Based on the analysis of the UNCLOS provisions, which prohibit the modification of the principle of freedom in the high seas and the principle of the common heritage of mankind in the Area, it is intended to propose a model of legal regime for the sustainable use of BBNJ to be adopted at the end of the current negotiations. Due to the provisions of UNCLOS, it is not possible for marine genetic resources beyond national jurisdiction to be uniformly ruled in the Agreement. Consequently, the genetic resources of the high seas should be transformed from res nullius into res communis, while those found in the Area, since they are already res communis humanitatis, should be submitted to the management of the International Seabed Authority.